2014
DOI: 10.1371/journal.pone.0089405
|View full text |Cite
|
Sign up to set email alerts
|

How Change of Public Transportation Usage Reveals Fear of the SARS Virus in a City

Abstract: The outbreaks of the severe acute respiratory syndrome (SARS) epidemic in 2003 resulted in unprecedented impacts on people's daily life. One of the most significant impacts to people is the fear of contacting the SARS virus while engaging daily routine activity. Here we use data from daily underground ridership in Taipei City and daily reported new SARS cases in Taiwan to model the dynamics of the public fear of the SARS virus during the wax and wane of the SARS period. We found that for each reported new SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 21 publications
4
73
0
Order By: Relevance
“…The spread of airborne infectious diseases such as SARS, H1N1, and MERS not only reduces people's outdoor activities [6,7,[17][18][19], but also affects a nation's economy, including retail sales. Globalization, which is characterized by frequent international movement of people and goods, has made the spread of such diseases to other countries unpredictable [20,21].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The spread of airborne infectious diseases such as SARS, H1N1, and MERS not only reduces people's outdoor activities [6,7,[17][18][19], but also affects a nation's economy, including retail sales. Globalization, which is characterized by frequent international movement of people and goods, has made the spread of such diseases to other countries unpredictable [20,21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this environment, the outbreak of the Middle East Respiratory Syndrome (MERS) that occurred in May 2015 in South Korea hit the domestic economy hard [5], bringing considerable changes. When infectious diseases such as MERS, Severe Acute Respiratory Syndrome (SARS), and H1N1 (subtype of influenza A virus) spread, people worry about possible infections that can affect their outdoor activities [6,7], and thus consumer behavior [8,9]. In fact, as concerns were mounting over MERS among economic players, there were visible signs of economic slowdown across the nation, including a reduction in demand for tourism, entertainment, leisure, and dining and a shrinking private education industry caused by a temporary shutdown of schools [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, emerging infectious diseases, such as SARS (Severe Acute Respiratory Syndrome), have posed serious threats to global public health [1]. With rapid spread and high mortality rates, these diseases often lead to tremendous public fear [2,3]. Ample studies have been reported concerning effective disease control in hospitals in such circumstances [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Once it occurs, both supply and demand may change. During the SARS epidemic in Taiwan, in contrast, however, the supply of medical services remained steady, while the demands for medical services decreased dramatically due to public fear [2,9,10]. Hence, medical claim data across the SARS period should be able to serve as the correct basis to estimate the demand elasticity of various types of medical services.…”
Section: Introductionmentioning
confidence: 99%
“…One of past well-recognized examples of such transportation-related global infection of a transmissible disease, SARS by severe acute respiratory syndrome coronavirus broke out in 2003, beginning with some infection on an airplane (Wang and Wu 2018). There have been many investigations concerning the effect of transportation (or population dispersal) on the spread of a transmissible disease, and especially conducted been many theoretical/mathematical studies taken account of such a possibility for some individuals to become infective during transportation in order to such an significant contribution of transport-related infection [as a recent review, see Walters et al (2018) and references therein; especially for the SARS virus transmission, see Wang (2014)]. Not only the particular transportation with a long travel, but also the human quotidian mobility as a common phase of the human activity can be considered as one of relevant factors that could cause the spread of a transmissible disease such as influenza (WHO 2018).…”
mentioning
confidence: 99%